The Left and The Right: a valid typology for a globalized world? - Navas García, Alejandro (2022)
The Left and the right are labels used in the political jargon to differentiate the ideology which supports them and which citizens also use as categories which allow them to locate themselves within the political horizon during elections period, besides being referents useful for orienting in regards to the options politicians adopt in their government action. But both right and left have evolved and currently political life goes beyond this ideological bipolarity and calls for an analysis which we will attempt.